Anticoccidial effect of methanolic root extracts of Cochlospermum planchonnii on birds experimentally infected with Eimeria maxima and Eimeria tenella - Chidubem Tobias Oyiga; Ikenna Michael Okpala; Ganiyu Efficience Aneru; Chukwunonso Francis Obi; Arinze Stephen Ezema; Wilfred Ikechukwu Ugwuoke; Ikenna Onyema Ezeh; Idika Kalu Idika; Chukwunyere Okwudiri Nwosu (Revue d’Elevage et de Médecine Vétérinaire des Pays Tropicaux)
-